Inventarisasi Pohon Sendang Tirto Gumitir Bagi Masyarakat Desa Sidomulyo - Anistya Khoeru Mashudha; Naurah Elsa Suwendra; Ahmad Sandy Lazuardi; Rohmad Aldi; Gusti Rizky; Riza Yuli Rusdiana (LPPM UNIVERSITAS DIAN NUSWANTORO, 2024)
Sendang Tirto Gumitir in Sidomulyo Village has a clear spring. The Sendang location is in the middle of a forest area. Around Sendang, there are many large-diameter trees with diverse and unique shapes and old age. The potential of Sendang Tirto Gumitir as educational tourism in its tree collection has not been implemented by tourism managers and village governments. Many villagers do not know the types and characteristics of trees in the Sendang area. The solution to overcome this problem is with manual and digital inventory activities of Sendang Tirto Gumitir. The results of the inventory of 23 trees in Sendang Tirto Gumitir obtained eight types of trees with the largest diameter, namely banyan trees (233 cm). Descriptions of information are on the village website, and information boards are attached to trees. The tree information board is integrated into the QR-Code. It is scanned with a mobile phone and contained tree information on the village website. Based on the educational side, QR-Code is useful in providing learning for visitors, the community, and students to gain access to tree information around Sendang Tirto Gumitir. The existence of tree inventory and digitization of information related to tree inventory is the first step for the village government to develop the Sendang Tirto Gumitir tourist attraction. Therefore, further activities recommended to expand the tree inventory area in Sendang Tirto Gumitir and add a description of the characteristics of tree species.